2021
DOI: 10.1007/s11482-020-09893-4
|View full text |Cite
|
Sign up to set email alerts
|

Work, Leisure, and Life Satisfaction for Employees with Physical Disabilities in South Korea

Abstract: Empirical studies on work-life balance (WLB) among employees without disabilities are abundant; in contrast, insufficient research exists on WLB and quality of life issues among employees with physical disabilities from Asian countries. This study used a nation-wide survey to examine how job satisfaction, leisure satisfaction, and satisfaction with family relationships, and satisfaction with friend relationships were positively associated with life satisfaction among employees with physical disabilities in Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…Many previous studies established links between leisure preferences and life satisfaction [ 23 , 31 ], links between life satisfaction and psychological capital [ 89 , 90 , 125 , 126 , 127 , 128 ], life satisfaction and mindfulness [ 129 , 130 ], or mindfulness and psychological capital [ 72 , 74 , 76 , 131 ]. Previous studies also examined links between several types of leisure activities and psychological capital [ 99 , 132 ] or links between some activities (meditation, physical activity) and mindfulness [ 9 , 133 , 134 , 135 ]. However, the links between leisure preferences, mindfulness, psychological capital, and life satisfaction have not previously been investigated in the same study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies established links between leisure preferences and life satisfaction [ 23 , 31 ], links between life satisfaction and psychological capital [ 89 , 90 , 125 , 126 , 127 , 128 ], life satisfaction and mindfulness [ 129 , 130 ], or mindfulness and psychological capital [ 72 , 74 , 76 , 131 ]. Previous studies also examined links between several types of leisure activities and psychological capital [ 99 , 132 ] or links between some activities (meditation, physical activity) and mindfulness [ 9 , 133 , 134 , 135 ]. However, the links between leisure preferences, mindfulness, psychological capital, and life satisfaction have not previously been investigated in the same study.…”
Section: Discussionmentioning
confidence: 99%
“…The construct of life satisfaction indicates a cognitive evaluation of one’s life and is a component of subjective wellbeing or happiness [ 4 , 94 , 95 ]. Numerous studies have demonstrated links between leisure and happiness [ 21 ], leisure and fulfillment [ 32 ], and leisure and life satisfaction [ 96 , 97 , 98 , 99 ].…”
Section: Introductionmentioning
confidence: 99%
“…Participants satisfied with either their jobs or leisure activities were 4.49 times more likely to be satisfied with their lives compared to those not satisfied with either their jobs or leisure activities. The findings of the authors suggest that managing a healthy balance between work and leisure may are critical to enhancing S-QOL among the population with disabilities (Kim et al 2021). The results of study revealed significantly higher satisfaction with leisure activities (p=0.020) and work/study (p=0.000) indicators in men elite athletes compare to women.…”
Section: Discussionmentioning
confidence: 82%
“…The group of 19-29 yrs.-old-men was significantly more satisfied with rest in leisure, work/study, and truth indicators compare to 45-59 yrs.-old-men. The results of the nationwide survey in South Korea demonstrated that job satisfaction, leisure satisfaction, and social relationships contributed significantly to the life satisfaction of people with physical disabilities (Kim et al 2021). Job satisfaction and leisure satisfaction were positively correlated.…”
Section: Discussionmentioning
confidence: 99%
“…All this added to their challenges amidst the pandemic. To maintain work-family balance, employees also used some strategies to achieve physical and emotional equilibrium that had a positive impact on their well-being, including resilience [65], self-compassion [66,67], and mindfulness-based practices [68], religiosity [69]. On the other hand, employers also played a positive role by job crafting [70,71], providing training opportunities for employees to facilitate their adaptation and enhance their efficacy to work remotely, and reassuring them about their job security [72].…”
Section: Introductionmentioning
confidence: 99%